The Athabasca Basin Region : People, Communities, Context - Tsannie, Joe; Johnson, Johanne (2017)
Explores the history of the Athabasca River Basin region and the Denesuline peoples of Northern Saskatchewan through traditional knowledge, legends, and stories. This includes the concept of spirit power derived from the spiritual relationship between people and animals, creation stories that speak of animal power, great floods and fires, and connection with other northern peoples.